Faith and Fury : the Temple Mount and the Noble Sanctuary : the story of Jerusalem's most sacred space - Cooper, Ilene (Roaring Brook Press, 2017)
"Temple Mount is a site where worlds meet, conflict arises, and history changes. Standing in the center of Jerusalem, it is a holy landmark for Jews, Muslims, and Christians alike, and has been the locus of many of the most important religious, social, and political upheavals of the last thousand years. Rumored to be the location of the Garden of Eden, Temple Mount dominates Jerusalem's Old City and contains the Dome of the Rock and the Western Wall, both of which attract millions of visitors and religious pilgrims each year.Veteran author Ilene Cooper explores the turbulent history of Jerusalem's famous Temple Mount in this timely, illustrated nonfiction offering"--